Let's play: Me and my AI‐powered avatar as one team. Issue 6 (1st April 2021) - Butt, Asad H.; Ahmad, Hassan; Goraya, Muhammad A. S.; Akram, Muhammad S.; Shafique, Muhammad N.
Abstract: Artificial intelligence (AI) tools have altered the gaming industry, thanks to their newly incepted functionalities, which have enhanced the consumer experience. Building on innovation diffusion theory, technology acceptance model, and flow theory, this study highlights an AI‐powered avatar concept. This study explores the roles of perceived easiness, usefulness, advantage, compatibility, enjoyment, customization, and interactivity in forming the gamers' intention to play with AI‐powered avatars. A survey data of 500 respondents from China having experience playing online video games is used to test the proposed hypotheses. The results offer significant support to the proposed relationships related to adopting an AI‐powered avatar and the consumers' psychological association with its adoption. Consequently, the results imply that AI‐powered avatars should allow gamers to customize, interact, and take assistance to move up levels with an enjoyable experience. Moreover, this study also suggests that digital technologies such as AI could be integrated into the gaming environment for a more pleasing and immersive experience.